A survival kit for the elementary school principal : with reproducible forms, checklists and letters - Bergman, Abby Barry (Paramus, N.J. : Prentice Hall, 1998)
Your role as principal. How to plan for the school year-setting goals and maintaining focus. Shared decision making-the key to a more effective school...
Keywords: Education; Elementary school principals; Elementary school principals -- United States -- Handbooks, manuals, etc; Education, Primary -- United States -- Administration -- Handbooks, manuals, etc